Ilisha elongata) WITH DIFFERENT PACKAGING DURING STORAGE - Gesang Nur Ikhlas; Sumarto Sumarto; Dewita Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis study aims to determine the effect of the best packaging on the quality of shredded gizzard (Ilhisa elongate) during storage at room temperature. The research was carried out through the process of making samples, observing during the shelf life, namely chemical content testing and organoleptic testing. The treatment factors are Low Density Polyethylene (LDPE), High Density Polyethylene (HDPE), and Polypropylene (PP) packaging. The oranoleptic data were analyzed by ANOVA. The data that have a very significant effect are tested by the BNJ follow-up test. The results obtained from the 2 test parameters obtained the highest organoleptic (visual) value (8.74); highest organoleptic (scent) (8.74); the highest organoleptic (texture) value (8.70); the highest organoleptic (taste) value (8.86). Therefore, the use of different packaging has a significant effect on the quality of the fermented fish (Ilhisa elongate) during storage at room temperature.    Keywords : floss, ilisha, organoleptic